2016
DOI: 10.7287/peerj.preprints.1807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examination of antimicrobial activity of selected non-antibiotic products

Abstract: A variety of pharmaceutical preparations, which are applied in the management of non-infectious diseases, have shown in vitro some antimicrobial activity. These drugs are called “non-antibiotics”. So far, a lot of attention has been focused on phenothiazines, thioxanthenes and other agents with affinities to cellular transport systems or agents showing other inhibition mechanism. Several authors confirmed that some non-antibiotics are “helper compounds”, which enhance the in vitro activity of certain antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
3
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 0 publications
1
81
3
2
Order By: Relevance
“…Similarly, Gram-negative bacteria such as Citrobacter spp, Pseudomonas aeruginosa, Klebsiella pneumoniae and Morganella morganii have been proven to be susceptible to SSRIs [120,123]. Notably, most of these bacteria are key players in induction of inflammation in the gut [99,100,[103][104][105][106][107][108].…”
Section: Gut Microbiota and Serotonin Productionmentioning
confidence: 99%
“…Similarly, Gram-negative bacteria such as Citrobacter spp, Pseudomonas aeruginosa, Klebsiella pneumoniae and Morganella morganii have been proven to be susceptible to SSRIs [120,123]. Notably, most of these bacteria are key players in induction of inflammation in the gut [99,100,[103][104][105][106][107][108].…”
Section: Gut Microbiota and Serotonin Productionmentioning
confidence: 99%
“…Interestingly, while supratherapeutic concentrations of acetaminophen, ibuprofen and diclofenac inhibit the growth of fungi (16)(17)(18)(19)(20), one study showed that at therapeutic concentrations, these antipyretics increase the growth of Candida spp. (21).…”
mentioning
confidence: 99%
“…These botanicals have previously been shown to have anti-S. aureus antimicrobial activity and have a strong history of traditional use against bacterial infections [20] [21] [22] [23] . Medically, bacteria continue to develop various mechanisms of resistance to circumvent the action of pharmaceutical drugs [18] . Botanicals may offer the medical and scientific community potential sources of novel antibiotics, since plants have a long history as sources of medicine [19] .…”
Section: Discussionmentioning
confidence: 99%